Selección de los animales en base a los caracteres de importancia económica en la producción de leche de bovinos acorde al objetivo de mejora genética en la parroquia de Belisario Quevedo. - Pilicita Cola, Andrea Belen (2023)
Dairy production inefficiency in Cotopaxi, is result by absence of genetic improvement program at breeders selection without technical-scientific criteria, becoming a problem faced by the dairy farmer. Therefore, the animals were evaluated based on traits of economic importance in the production of bovine milk according to the genetic objective improvement on Belisario Quevedo parish. For this purpose 14 farms belonging to research project were evaluated, where the animals were measured according following parameters: gain weight, milk production, milk density and mastitis analysis with CMT. Thanks to all the gathered information from production units, the objective of genetic improvement was established, which is gain weight, milk production and milk quality in order to satisfy and meet the producers’ needs. Thirty percent of the samples are cows in production, while 70% correspond to cattle of all ages, including females and males. Based on the genetic variability of animals weight in relation to milk production, it was determined that weight is independent from number of iters of milk produced by a cow. A cow weighing 360 kg produces 14.68 liters/day; in relation to a cow weighing 529.25, it produces 16 liters/day. In terms of density, the average of 28.49 (1,028 g/ml), complying in a certain way with the NTE INEN 9 standards as a requirement for physicochemical quality control of milk. Likewise, the gain weight with vitamins administration, in which the animals had a significant increase in weight month to month with an average range of 9.83 kg. Finally, 3 animals were selected that met the established criteria. With this, it can be deduced that the implementation of a genetic improvement program is a key element for optimization of production systems and increased animal productivity, influenced by genetic and environmental conditions.